The corona between cycles and paths - S. Nada; A. Elrokh; E.A. Elsakhawi; D.E. Sabra (Journal of the Egyptian Mathematical Society, 2017)
A graph is said to be cordial if it has a 0–1 labeling that satisfies certain properties. The corona G1⨀G2 of two graphs G1(with n1 vertices and m1 edges) and G2 (with n2 vertices and m2 edges) is defined as the graph obtained by taking one copy of G1 and n1 copies of G2, and then joining the ith vertex of G1 with an edge to every vertex in the ith copy of G2. In this paper we investigate the cordiality of the corona between cycles Cn and paths Pn, namely Cn⨀Pm.